2002
DOI: 10.1016/s0895-7061(01)02319-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of arterial stiffness; definitions and reference values

Abstract: Arterial stiffening is the most important cause of increasing systolic and pulse pressure, and for decreasing diastolic pressure beyond 40 years of age. Stiffening affects predominantly the aorta and proximal elastic arteries, and to a lesser degree the peripheral muscular arteries. While conceptually a Windkessel model is the simplest way to visualize the cushioning function of arteries, this is not useful clinically under changing conditions when effects of wave reflection become prominent. Many measures hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
780
7
70

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,000 publications
(883 citation statements)
references
References 86 publications
26
780
7
70
Order By: Relevance
“…Arterial stiffening has been associated with hypertension, dyslipidemia, diabetes mellitus, and atherosclerosis 29, 30, 31, 32, 33. The buffering action of the systemic arterial system is reduced with rAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial stiffening has been associated with hypertension, dyslipidemia, diabetes mellitus, and atherosclerosis 29, 30, 31, 32, 33. The buffering action of the systemic arterial system is reduced with rAC.…”
Section: Discussionmentioning
confidence: 99%
“…The buffering action of the systemic arterial system is reduced with rAC. rAC is a major contributor to the development of systolic hypertension, contributing to LV afterload and decreased coronary flow during diastole, and it has been shown to be a strong predictor of LV dysfunction and adverse events 30, 31, 32, 33, 34. Patients with AS already have increased LV afterload because of valvular stenosis, and it has been demonstrated that rAC has a significant additive effect and contributes to LV dysfunction and occurrence of adverse outcomes 22, 35.…”
Section: Discussionmentioning
confidence: 99%
“…The ageassociated stiffening results in increased central systolic blood pressure (SBP) because the cushioning function to accommodate the systolic volume ejected by the left ventricle cannot be performed without a significant increase in peak blood pressure (BP). 2 The contribution of reflected pulse wave is of critical importance in this respect. When arteries are compliant and elastic, the reflected wave merges with the outgoing wave in the late systolic or diastolic phase and there is little or no effect on central SBP.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although there are many measures to quantify stiffness, none of them is a gold standard, but approximations. 16,17 It is believed that the most reliable (and still probably the best) measure of arterial stiffness is pulse wave velocity (PWV). 16 PWV is known to be associated with age, gender, blood pressure (BP), heart rate, salt intake, genetic factors and others.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It is believed that the most reliable (and still probably the best) measure of arterial stiffness is pulse wave velocity (PWV). 16 PWV is known to be associated with age, gender, blood pressure (BP), heart rate, salt intake, genetic factors and others. Although BP is one of the strongest factors influencing PWV, varying correlation coefficients have been reported between the various PWV (aorta-leg-arm) and BP (systolic, diastolic, mean, pulse) using non-invasive methods.…”
Section: Introductionmentioning
confidence: 99%